2008
DOI: 10.1089/ees.2007.0048
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Methyl Orange in Water by Samarium-Doped TiO2

Abstract: A series of Sm-doped TiO 2 nanoparticles were prepared by the sol-gel method and characterized with X-ray diffraction (XRD), transmission electron microscope (TEM), and ultraviolet-visible diffuse reflectance spectra (DRS). Their photacatalytic activities were studied by photodegradation methyl orange in water under UV and simulant solar light irradiation, respectively. The results showed that Sm doping led to the crystal expansion and matrices distortion. Sm doping restrained a crystal size increase, which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…This is due to an extra energy level formed just below the conduction band of titania with higher redox potential than that of oxygen. 21 The creation of oxygen vacancies was also consistent with the results found by Xiao et al, 23 in which Sm 3+doped titania were prepared by sol-gel auto-combustion technique, where combustible organics are used to drive the synthesis. Several other studies followed from Xu et al 9 and most are in agreement with how rare-earth metals form oxides on the outside of TiO 2 .…”
Section: Single Rare-earth Metal Dopingsupporting
confidence: 87%
See 2 more Smart Citations
“…This is due to an extra energy level formed just below the conduction band of titania with higher redox potential than that of oxygen. 21 The creation of oxygen vacancies was also consistent with the results found by Xiao et al, 23 in which Sm 3+doped titania were prepared by sol-gel auto-combustion technique, where combustible organics are used to drive the synthesis. Several other studies followed from Xu et al 9 and most are in agreement with how rare-earth metals form oxides on the outside of TiO 2 .…”
Section: Single Rare-earth Metal Dopingsupporting
confidence: 87%
“…Hydroxide ions act as hole-traps which in turn delay the undesired recombination reaction. Shi et al 21 found samarium (Sm) doping created oxygen vacancies which were confirmed by photoluminescence. The synthesis parameters were almost identical to those of Xu et al, 9 however, acetic acid was used in the preparation of the sol instead of nitric acid.…”
Section: Single Rare-earth Metal Dopingmentioning
confidence: 95%
See 1 more Smart Citation
“…145,146 Nevertheless, some counter examples, such as samarium and gadolinium, have been reported. 145,147,148 The formation of lanthanide oxides, or integrating with TiO 2 matrix also depends on the employed approach for doping. 145 In view of the lanthanide oxide formation during the calcination step, Ti can insert and supersede the rare-earth metal ions.…”
Section: Modification Of Tiomentioning
confidence: 99%
“…Nevertheless, the application of TiO 2 as a photocatalyst for visible light-induced chemical reactions was hampered by its large band-gap energy (3.2 eV for anatase TiO 2 ), which requires ultraviolet (UV) light to activate and leads to the lower energy efficiency. To increase the activity of TiO 2 and reduce the band-gap energy to the visible light range, the modification of the catalysts has also been attempted by doping them with various transition metals (Yamashita et al, 2003;Zhu et al, 2006;Shi et al, 2008;Surolia et al, 2010), including vanadium. Recent reports have indicated that vanadium doping provides a promising strategy to improve the photoactivity of titania under visible light.…”
mentioning
confidence: 99%